Traditional First Nations and Métis Healing Methods: Do They Foster Emotional, Mental and Spiritual Healing? - Binsfeld, Sarah 1984- (2016)
Critical Incident Technique (CIT) (Flanagan, 1954) was used to explore the efficacy of traditional First Nations and Métis healing methods in terms of emotional, mental and spiritual healing among self-identified First Nations and Métis students at the University of Saskatchewan. Three participants were interviewed for this study. Data was analyzed using McCormick’s (1997) ten themes as well as thematic analysis. Findings correlated with McCormick’s (1997) themes, and no new ones were added and none omitted. The themes and data were discussed in relation to Smart’s (1998) Seven Dimensions of Religion, in order to anchor the findings in a theoretical framework. Recommendations for future research as well as recommendations for counsellors and psychologists regarding integration of traditional First Nations and Métis healing methods in counselling are included.